2020
DOI: 10.3390/ma13071673
|View full text |Cite
|
Sign up to set email alerts
|

Diatoms Biomass as a Joint Source of Biosilica and Carbon for Lithium-Ion Battery Anodes

Abstract: The biomass of one type cultivated diatoms (Pseudostaurosira trainorii), being a source of 3D-stuctured biosilica and organic matter—the source of carbon, was thermally processed to become an electroactive material in a potential range adequate to become an anode in lithium ion batteries. Carbonized material was characterized by means of selected solid-state physics techniques (XRD, Raman, TGA). It was shown that the pyrolysis temperature (600 °C, 800 °C, 1000 °C) affected structural and electrochemical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…The obtained forms are similar to the forms of calcium carbonates obtained in the study of El-Naas et al [ 73 ]. Additionally, in our previous work, the presence of calcium carbonates in the biomass of Pseudostaurosira trainorii diatoms was confirmed by XRD, TG and FTIR analysis [ 74 ]. The significant carbon content in the sample indicates the presence of the organic part of the diatom cell.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The obtained forms are similar to the forms of calcium carbonates obtained in the study of El-Naas et al [ 73 ]. Additionally, in our previous work, the presence of calcium carbonates in the biomass of Pseudostaurosira trainorii diatoms was confirmed by XRD, TG and FTIR analysis [ 74 ]. The significant carbon content in the sample indicates the presence of the organic part of the diatom cell.…”
Section: Resultsmentioning
confidence: 87%
“…All the samples presented a significant mass loss (from 3% for N_w to 22% for N_g) in the range from about 400 °C to about 700 °C, corresponding to strong exothermic peaks in the DSC curves. In fact, this loss may be due to the decomposition of organic matter of diatom biomass [ 74 ] containing molecules such as lipids and proteins [ 100 , 101 ]. In addition, for materials doped with titanium, this range coincides with the temperature range (400–480 °C), corresponding to the amorphous transformation of TiO 2 into anatase form [ 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…The specific capacity is as high as 1200 mA h g –1 after 5 cycles and remains at 924 mA h g –1 after 200 cycles with a Coulombic efficiency of almost 100%, which is obviously superior to that of the DBS anode (Figure S3) and at a relatively high level in comparison with reported synthetic and biomass-based SiO 2 anodes (Table S1). ,,,,, The microstructure and morphologies of the C@DBS anode after cycling were studied by ex situ SEM. As revealed in Figure S4, the porous structure of C@DBS was well preserved due to the protection from the carbonaceous component distributed around silica.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the vast number of examples where DE is used as a template material, only a few reports have focused on the direct implementation of DE silica into negative electrodes for LIBs. [27][28][29][30] Experimental results have shown that oval-shaped diatoms with an average diameter of 5 mm embedded in a carbonaceous matrix can reach discharge capacities of 460 mA h g À1 aer 70 cycles at 40 mA g À1 . 30 A different work on ball-milled frustules with a mean particle size of 3 mm, reported a capacity of 679 mA h g À1 aer 50 cycles displayed by carbon coated sea-hauled diatoms.…”
Section: Introductionmentioning
confidence: 99%